2021
DOI: 10.1038/s41598-021-87533-z
|View full text |Cite
|
Sign up to set email alerts
|

TMS-EEG signatures of glutamatergic neurotransmission in human cortex

Abstract: Neuronal activity in the brain reflects an excitation–inhibition balance that is regulated predominantly by glutamatergic and GABAergic neurotransmission, and often disturbed in neuropsychiatric disorders. Here, we tested the effects of a single oral dose of two anti-glutamatergic drugs (dextromethorphan, an NMDA receptor antagonist; perampanel, an AMPA receptor antagonist) and an L-type voltage-gated calcium channel blocker (nimodipine) on transcranial magnetic stimulation (TMS)-evoked electroencephalographic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 60 publications
3
67
0
Order By: Relevance
“…Interestingly, anti-glutamatergic drugs such as perampanel, an AMPA-receptor antagonist, could be eventually helpful in this condition. Indeed, recent TMS 63 and SEP studies 64 have demonstrated its effect in increasing motor thresholds in the HC and reducing SEP amplitude and HFOs area in the JME, thus raising the possibility of normalizing excitatory circuits in the sensorimotor cortex with possible beneficial effects on cortical tremor in FAME2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, anti-glutamatergic drugs such as perampanel, an AMPA-receptor antagonist, could be eventually helpful in this condition. Indeed, recent TMS 63 and SEP studies 64 have demonstrated its effect in increasing motor thresholds in the HC and reducing SEP amplitude and HFOs area in the JME, thus raising the possibility of normalizing excitatory circuits in the sensorimotor cortex with possible beneficial effects on cortical tremor in FAME2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results from using the present method to remove PEPs from early (i.e., within the first 90 ms) EEG responses to TMS of motor cortex are mostly in agreement with previous reports (for review, ( Komssi and Kahkonen, 2006 ; Hill et al., 2016 ; Hallett et al., 2017 )). However, a close inspection shows that only the P30 and the N45/P45 have been clearly described, while a dipolar P70/N70 with the P70 expressed in bilateral prefrontal cortex and the N70 in parietal cortex ipsilateral to TMS was not described in uncontrolled or incompletely sham-controlled studies ( Komssi et al., 2004 ; Bonato et al., 2006 ; Premoli et al., 2014 ; Cash et al., 2017 ; Gordon et al., 2018 ; Darmani and Ziemann, 2019 ; Ahn and Frohlich, 2021 ; Belardinelli et al., 2021 ), with the exception of one study that however failed to demonstrate the preceding dipolar N45/P45 response ( Premoli et al., 2014 ). A recent study has described a negative deflection at around 45 ms and a positive deflection at 60 ms, respectively N45 and P60, which were located in the ipsilateral somatosensory cortex, whereas the P30 was localized in the stimulated motor cortex, in line with our present findings ( Ahn and Frohlich, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The P25 amplitude is decreased by voltage-gated sodium channel blockers (carbamazepine) ( Darmani et al, 2019 ), similar to their decreasing action on excitability of the corticospinal neurons as reflected by decrease in motor evoked potential amplitude. The N45 amplitude is decreased by positive allosteric modulators at GABAA receptors (alprazolam, diazepam, zolpidem) ( Premoli et al, 2014 ) and NMDA receptor antagonists (dextromethorphan) ( Belardinelli et al, 2021 ), suggesting that the N45 reflects a balance of GABAAergic inhibitory and glutamatergic excitatory neural activity. The P60 (P70) potential is decreased by AMPA receptor antagonists (perampanel), providing evidence for this potential to represent fast ionotropic glutamatergic neural activity ( Belardinelli et al, 2021 ).…”
Section: Tms-eegmentioning
confidence: 99%
“…The N45 amplitude is decreased by positive allosteric modulators at GABAA receptors (alprazolam, diazepam, zolpidem) ( Premoli et al, 2014 ) and NMDA receptor antagonists (dextromethorphan) ( Belardinelli et al, 2021 ), suggesting that the N45 reflects a balance of GABAAergic inhibitory and glutamatergic excitatory neural activity. The P60 (P70) potential is decreased by AMPA receptor antagonists (perampanel), providing evidence for this potential to represent fast ionotropic glutamatergic neural activity ( Belardinelli et al, 2021 ). The N100 amplitude at the site of motor cortex stimulation is increased by GABAB receptor agonists (baclofen) ( Premoli et al, 2014 ), corroborating the view that this potential reflects long-lasting GABABergic cortical inhibition.…”
Section: Tms-eegmentioning
confidence: 99%
See 1 more Smart Citation